国际法委员会年鉴 2014年, 第一卷 - UN ILC (United Nations, 2022)
The Yearbook of the International Law Commission contains the official records of the Commission and is an indispensable tool for the preservation of the legislative history of the documents emanating from the Commission, as well as for the teaching, study, dissemination and wider appreciation of the efforts undertaken by the Commission in the progressive development of international law and its codification. Volume I reproduces the summary records of the Commission's annual sessions.